1995
DOI: 10.1007/bf01271543
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dopamine D3 preferring compounds on conditioned place preference and intracranial self-stimulation in the rat

Abstract: Compounds showing an in vitro binding preference for the dopamine D3 receptor were tested in two models designed to assess positive reinforcement in the rat: intracranial self-stimulation (ICSS) and conditioned place preference (CPP). R-(+)-7-OH-DPAT, a D3 preferring agonist, inhibited ICSS behaviour over a wide dose range. At higher doses, a facilitation of ICSS was seen. In the CPP model, 7-OH-DPAT was inactive except at the highest dose where a significant change in preference was seen. A dose of R-(+)-7-OH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
16
0
4

Year Published

1996
1996
2014
2014

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 34 publications
5
16
0
4
Order By: Relevance
“…However, in other studies, U-99194A has been shown to support CPP (Kling-Petersen et al, 1995;Gyertyán and Gál, 2003). On the other hand, numerous convergent studies indicated that distinct to BP 897, D 3 R full agonists shared with D 1 /D 2 nonselective and D 2 selective agonists the capacity to establish CPP (Hoffman and Beninger, 1988;Papp, 1988;Mallet and Beninger, 1994;Kling-Petersen et al, 1995;Khroyan et al, 1997), although some inconsistencies also exist in this respect (Rodríguez de Fonseca et al, 1995;Khroyan et al, 1997;Gyertyán and Gál, 2003). In fact, D 3 R-preferring agonists may exhibit biphasic effects on place conditioning.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…However, in other studies, U-99194A has been shown to support CPP (Kling-Petersen et al, 1995;Gyertyán and Gál, 2003). On the other hand, numerous convergent studies indicated that distinct to BP 897, D 3 R full agonists shared with D 1 /D 2 nonselective and D 2 selective agonists the capacity to establish CPP (Hoffman and Beninger, 1988;Papp, 1988;Mallet and Beninger, 1994;Kling-Petersen et al, 1995;Khroyan et al, 1997), although some inconsistencies also exist in this respect (Rodríguez de Fonseca et al, 1995;Khroyan et al, 1997;Gyertyán and Gál, 2003). In fact, D 3 R-preferring agonists may exhibit biphasic effects on place conditioning.…”
Section: Discussionmentioning
confidence: 83%
“…Preclamol, a partial agonist at D 2 autoreceptors, and the D 3 R antagonists, l-nafadotride (B10-fold selective for rat D 3 R over D 2 R, in vivo (Griffon et al, 1995)), U-99194A (B20-fold selective for D 3 R vs D 2 R expressed in CHO cells (Waters et al, 1993)), and SB-277011-A (4100-fold selective for rat D 3 R over D 2 R expressed in CHO cells (Reavill et al, 2000)), seem devoid of incentive properties (Chaperon and Thiébot, 1996;Kivastik et al, 1996;Boyce and Risinger, 2002;Vorel et al, 2002;Gyertyán and Gál, 2003). However, in other studies, U-99194A has been shown to support CPP (Kling-Petersen et al, 1995;Gyertyán and Gál, 2003). On the other hand, numerous convergent studies indicated that distinct to BP 897, D 3 R full agonists shared with D 1 /D 2 nonselective and D 2 selective agonists the capacity to establish CPP (Hoffman and Beninger, 1988;Papp, 1988;Mallet and Beninger, 1994;Kling-Petersen et al, 1995;Khroyan et al, 1997), although some inconsistencies also exist in this respect (Rodríguez de Fonseca et al, 1995;Khroyan et al, 1997;Gyertyán and Gál, 2003).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Pretreatment with low doses of 7-OH-DPAT shifts the cocaine self-administration dose-response curve to the left, suggesting enhancement of the reinforcing effects of cocaine . Furthermore, a low dose of 7-OH-DPAT co-administered with d-amphetamine potentiates d-amphetamine-induced increases in intracranial self-stimulation (Kling-Peterson et al 1995). However, effects of 7-OH-DPAT on psychomotor stimulant-CPP have not been examined.…”
Section: Introductionmentioning
confidence: 95%
“…Selective D1 agonists such as SKF38393 [(6)-1-phenyl-2,3,4,5-tetrahydro-(1H)-3-benzazepine-7,8-diol hydrobromide], SKF82958 (3-allyl-6-chloro-1-phenyl-1,2,4,5-tetrahydro-3-benzazepine-7,8-diol), and A77636 [(1R,3S)-3-(1-adamantyl)-1-(aminomethyl)-3,4-dihydro-1H-isochromene-5,6-diol] have been reported to facilitate ICSS in some studies (Nakajima and O'Regan, 1991;Ranaldi and Beninger, 1994;Carr et al, 2001;Gilliss et al, 2002;Malanga et al, 2008), but the magnitude of facilitation is generally weak and may be accompanied by evidence for impaired performance, and other studies have reported only depression by D1 agonists (Hunt et al, 1994;Baldo et al, 1999). Similarly variable effects have been obtained with D2/3 agonists such as bromocriptine, quinpirole, quinelorane, 7-OH-DPAT [7-hydroxy-2-(di-n-propylamino)tetralin], and U99194A (5,6-dimethoxy-N,N-dipropyl-2,3-dihydro-1H-inden-2-amine) (Nakajima and O'Regan, 1991;Hunt et al, 1994;Ranaldi and Beninger, 1994;Kling-Petersen et al, 1995;Depoortere et al, 1996;Hatcher and Hagan, 1998;Carr et al, 2001Carr et al, , 2002Malanga et al, 2008). For example, quinpirole facilitated ICSS in some studies (Ranaldi and Beninger, 1994;Carr et al, 2001), depressed ICSS in other studies (Rady et al, 1994;Hatcher and Hagan, 1998), and produced variable effects across doses and different ICSS rates in yet other studies (Nakajima and O'Regan, 1991;Depoortere et al, 1996;Malanga et al, 2008).…”
Section: Icss In Abuse Potential Testingmentioning
confidence: 99%